EVALUATION OF A DISTANT LEARNING COURSE ON HEPATITIS C - Aparecida Jacomini, Regiane; Piai, Thaís Helena; Moralez de Figueiredo, Rosely (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Hepatitis C is a recent disease—it appeared just over a decade ago—and has demanded that nursing professionals study and constantly update their knowledge so as to provide effective assistance. Information technologies, in turn, are increasingly present in today’s world and can greatly facilitate the performance of everyday activities. Objective: this study aims at evaluating a distant education (DE) course on hepatitis C offered to nursing students. Methodology: it is an end-of-course assignment based on an applied research project of a transversal nature. Its participants are thirty-seven 3rd and 4th-year nursing students from Federal University of São Carlos, Brazil. The DE course was offered on a MOODLE virtual learning platform. Results and discussion: out of the thirty-seven students that initially showed interest in the course and consented to participate in the research only twenty-nine enrolled in the module (78%) and thirteen completed it (45%). The average number of accesses to the virtual environment was 114, while this number reached 515 in the beginning module of the course and 141 in the final one. The participants’ final knowledge on hepatitis C improved by 50% when compared to the results of a pre-assessment. Their final average grade was 7.5 (0-10 scale). The drop-out rate in this educational mode is still quite high (55%) — its main causes being the participants’ deficient organization of study time and difficulties related to prompt access to computers and Internet services. Conclusions: The results of this study suggest that DE is a viable strategy for the continued education of health professionals. To this end, however, variables such as students’ study time and ready access to computers and the Internet should be carefully dimensioned.